Quantitative Assessment of the Relationship between Land Management Practices, Financial Literacy, Supply Chain Integration, and Profitability in Agribusiness Enterprises - Riswandi, D. Iwan; Abidin, Zainal (International Journal of Business, Law, and Education, 2024)
This research explores the relationship between land management practices, financial literacy, supply chain integration, and profitability in agribusiness enterprises. Using a quantitative approach with a sample size of 150 respondents, the study investigates the influence of these factors on profitability. Results indicate significant positive relationships between land management practices, financial literacy, supply chain integration, and profitability. Sustainable land management practices enhance productivity and environmental stewardship, while financial literacy empowers stakeholders to make informed financial decisions and access capital markets. Additionally, supply chain integration improves operational efficiency and reduces costs. These findings highlight the importance of integrating good practices in farming, finance, and supply chain management for long-term success in the agricultural sector.